The Role of TPI Murante Fish Auction Place in the Skipjack Fish (Katsuwonus pelamis) Trade in Luwu Regency - Andi Mappiasse, Nuraini; Gosari, Benny Audy Jaya; Cangara, Arie Syahruni; Adhawati, Sri Suro; Wahid, Abd. (PONGGAWA : Journal of Fisheries Socio-Economic, 2023)
This study aims to determine the role of the Murante Fish Auction Place in the trade process of skipjack tuna (K. pelamis), the trading process of skipjack tuna (K. pelamis) at the Murante Fish Auction, and the advantages and disadvantages of trading skipjack tuna (K. pelamis) at the Murante Fish Auction Place. This research was conducted in April 2021 at TPI Murante, Luwu Regency. The type of research used is survey research with a qualitative nature. The population in this study were TPI managers, ship owners, and fish traders using the census method where the sample was taken from the entire population that was used as the research sample. The data sources used are primary data and secondary data then processed using a Likert scale and analyzed using qualitative descriptive analysis. The results showed that the role of TPI Murante, namely as a place for boats to dock and a place for quality development of fishery products, had a fairly good level of role and as a place for skipjack tuna trading as well as a place for landing fish and loading and unloading catches had a good role. The advantages of trading skipjack tuna at the Murante Fish Auction are that the conditions for participating in the skipjack trade are easy to fulfill, do not delay the execution of skipjack tuna trade, and have trading facilities such as trading buildings, scales, barriers, and clean water. For lack of skipjack trade at the Murante Fish Auction, among others, TPI lost retribution, uncertain trading times, and lack of coolboxes to place fish.